Splenic Anomalies of Shape, Size, and Location: Pictorial Essay - Adalet Elcin Yildiz; Macit Orhan Ariyurek; Musturay Karcaaltincaba (The Scientific World Journal)
Spleen can have a wide range of anomalies including its shape, location, number, and size. Although most of these anomalies are congenital, there are also acquired types. Congenital anomalies affecting the shape of spleen are lobulations, notches, and clefts; the fusion and location anomalies of spleen are accessory spleen, splenopancreatic fusion, and wandering spleen; polysplenia can be associated with a syndrome. Splenosis and small spleen are acquired anomalies which are caused by trauma and sickle cell disease, respectively. These anomalies can be detected easily by using different imaging modalities including ultrasonography, computed tomography, magnetic resonance imaging, and also Tc-99m scintigraphy. In this pictorial essay, we review the imaging findings of these anomalies which can cause diagnostic pitfalls and be interpreted as pathologic processes.